Et depotfund fra yngre bronzealder – Nymølle Bro ved Lisbjerg - Frost, Lise (Kuml, 2010)
A Late Bronze Age hoard from Nymølle Bro near Lisbjerg The hoard from Nymølle Bro near Lisbjerg, NW of Århus, is a multi-type dry-land assemblage comprising 13 objects, and combined from the equipment of at least three individuals. Chronologically, the find lies around the transition between periods IV and V of the Late Bronze Age (c. 1000-900 BC). It comprises three hanging vessels, a belt ornament, two miniature fibulas, three fibulas (two piece), a large awl, two casting jets and a piece of casting waste (see fig. 1). Overall, there are not many single, uni- or multi-type depositions from the Late Bronze Age in the Århus area (see fig. 2). The find is therefore remarkable both for the local area and in general as there are only three examples of hoards containing the costume equipment of more than two women from the whole of Denmark. The hoard was discovered in August 1933 by a group of labourers working in a gravel pit to the east of the farm of Nymølle near Lisbjerg. Accordingly, like so many other hoards, it turned up by chance and information concerning the find circumstances is scant. It has, however, been possible to locate the find spot. This lies in undulating terrain to the south, on a small promontory facing down towards the river Egå, and the steep and uneven sub-glacial stream trench at Kasted (see fig. 3). The Nymølle assemblage is well preserved, with a combined weight of 1345 g. With respect to date, two of the hanging vessels (figs. 6 and 8), the belt ornament (fig. 9) and two of the fibulas (figs. 10 and 12), show clear period V features in their form and/or ornamentation. The dating of the artefacts therefore lies at the transition between periods IV and V. However, the fact that period V motifs appear on artefact types from period IV just shows that assignation to type is difficult with respect to bronze ornaments such as belt ornaments and hanging vessels because these generally comprise a uniform group in which various form and style traditions occur intermixed. At the same time, a chronologically fluid transition between periods IV and V fits very well with the record available from grave finds. Furthermore, artefacts in hoards, in particular, can be expected to show a gradual chronological development because they presumably represent objects belonging to several people/families which were deposited at one time. Bronzes are also artefacts with a long life. On the distribution maps (figs. 2 and 20), the Nymølle find is, however, marked with a period IV symbol. This is partly because, for the sake of visual clarity, it is necessary not to use too many chronological symbols, partly because period IV is the date assigned to the find in the literature. In addition to a lump of bronze, the find also contains two so-called casting jets, representing remains from the casting process (fig. 17). One of them (to the right on fig. 17) has two pouring channels and appears to originate from a hollow-cast socketed object, perhaps a celt (see fig. 18). The other casting jet in the assemblage (to the left on fig. 17) has two broad, flat casting deadheads. In this case it has not proved possible to make any suggestion concerning the object to which the jet was originally attached during casting. However, the piece is interesting in that it displays clear file marks showing that it has been filed using a narrow polishing stone, probably of flint. The robust bronze awl in the assemblage (fig. 19) can obviously also be seen in connection with casting and ornamentation. Perhaps it was used as a punch, or these heavy awls could have been used as a kind of decorating and modelling tool in connection with ornamental work in wax. Figure 20 shows the distribution for the whole country of hoards from the Late Bronze Age containing casting material and/or awls. The find circumstances and content vary in the same way as with other artefact types in hoards. Consequently, it is not immediately possible to identify any general characteristics of hoards with this particular content. However, it is important to focus greater attention on finds linked with technology and crafts, as this is generally a neglected area. Relative to the analysis of the individual artefacts in the Nymølle assemblage, it should be emphasised that there is still a lack of knowledge concerning basic technical details relating to casting. But in relation to the form of the ornamentation on, for example, the hanging vessels, the conclusion drawn from radiographs and from related finds is that neither cast nor punched ornamentation was universal. The Nymølle find belongs to a group of just over 200 Danish multi-type hoards from Bronze Age periods IV and V, the content of which is dominated by sets of female ornaments and costume equipment. Furthermore, the find is special because it contains parts of sets from at least three individuals as well as casting material and tools. The content therefore points in several directions at once. This is a typical feature of hoards which, with respect to both content and find circumstances, are very diverse and thereby difficult to interpret and categorise. The artefact assemblage constituting the Nymølle find represents, among other things, components of costume equipment belonging to a small group of women who could have been from the same family and/or have been linked socially and religiously. In themselves, however, the artefacts make it difficult to talk in terms of sets of artefacts and, thereby, the number of people involved. This would require new investigations of wear, alloy composition, ornamentation and tool marks. Many researchers have attempted to characterise hoards in various ways, for example as sacral and profane depositions. However, as the finds are very diverse it is often possible to classify them into several categories. Although it is clear that, especially in the Late Bronze Age, a definite distinction was made between artefacts which ended up in hoards and in graves, respectively. Accordingly, the two find groups supplement each other and appear to illustrate two different, mutually connected ritual impressions. This also applies, for example, in relation to the use of the landscape where there are indications that different places have different significance. In general, barrows are the typical burial places relative to bogs and wetlands as typical localities for depositions. Accordingly, it is important to see hoards in relation to the other categories of Bronze Age finds in a local landscape-archaeological perspective. Berta Stjernquist has, in several contexts, studied complex sacrificial sites in a diachronic settlement-archaeological perspective. She has, for example, attempted to divide the finds up into an individual and an official cult. The former could, for example, be the deposition of a pottery vessel containing food from a single household, whereas the official cult would have involved several participants and a content comprising, for example, ornaments, weapons and/or cultic artefacts. With respect to a find such as Nymølle, containing ornaments from several individuals, the deposition appears most obviously to be an expression of a communal undertaking by an area or district. Seen in the light of the general source-related problems pertaining to hoards, where it is often the case that, as at Nymølle, one is faced with a chance find lacking basic information concerning the find context, the landscape can provide part of the key to a better understanding of the finds and their relationship to the cultural landscape as a whole. Unfortunately, apart from the round barrows, a couple of settlement traces and a cup-marked stone in Lisbjerg Church there are as yet, however, no other Late Bronze Age finds from Lisbjerg parish or neighbouring parishes close to the find site. In the case of the Nymølle find, there is no information concerning the depth at which the artefacts lay or whether they were arranged in a certain way, wrapped and so on. Neither do we know precisely where the find was deposited, but the find site was on a south-facing slope running down towards the river Egå. About 100 m to the east of the find site, the river meets a stream Koldkær Bæk, which also forms part of the northern boundary between Skejby, Kasted and Lisbjerg parishes. Egå has its source in a bog Geding Mose, about 2.5 km east of the find site. The river runs along the floor of a narrow valley with steep sides which, further to the east, widens out into the Stone Age Lystrup Fjord and its mouth into the Bay of Århus. During the Bronze Age it was probably possible to sail as far inland as the crossing at Lisbjerg Bro, where the landscape alters and the river changes character and becomes narrower. About 900 m further to the west of Lisbjerg Bro lies the Nymølle Bro find site, where there is a natural crossing place over Egå. The site must therefore have been of great significance relative to communication and transport. Judging from the topography to the south of the find site and the river, where both to the east and west there are several boggy and impassable areas, there was also a relatively great distance to alternative crossings. Hoards typically lie in close association with watercourses, which of course is due to the fact that this is where bogs and wetlands are also located. But their location by rivers is also interesting relative to communication. Closer investigations of the location of the hoards in the landscape often show that the finds were actually deposited in places which topographically appear to have been central relative to the infrastructure. The location of hoards in bogs and wetland areas should therefore not necessarily be seen as being peripheral, lying far away from everything associated with everyday life. An important location relative to routes of communication need not be in conflict with the hoards’ possible connection to religion and rituals. In any case, this concept is very consistent with the Bronze Age as a society in which ritual aspects seem to be woven into everyday life in various ways –including as markers in the landscape. Perhaps it was in such communicatively significant places that people met in connection with rituals, or perhaps it was even essential to carry out depositions in places located in border areas and where crossings had to be made. The hoards constitute a strange and difficult find group which can, on the face of it, appear peripheral in their location. However, seen in a landscape context, there is great potential for the logical inclusion of the finds as part of the structure of the cultural and ritual landscape of the Bronze Age. Lise Frost Moesgård Museum